Design, synthesis, and biological evaluation of potent FAK-degrading PROTACs. (31st December 2022) - Qin, Qiaohua; Wang, Ruifeng; Fu, Qinglin; Zhang, Guoqi; Wu, Tianxiao; Liu, Nian; Lv, Ruicheng; Yin, Wenbo; Sun, Yin; Sun, Yixiang; Zhao, Dongmei; Cheng, Maosheng
Abstract: FAK mediated tumour cell migration, invasion, survival, proliferation and regulation of tumour stem cells through its kinase-dependent enzymatic functions and kinase-independent scaffolding functions. At present, the development of FAK PROTACs has become one of the hotspots in current pharmaceutical research to solve above problems. Herein, we designed and synthesised a series of FAK-targeting PROTACs consisted of PF-562271 derivative 1 and Pomalidomide. All compounds showed significant in vitro FAK kinase inhibitory activity, the IC50 value of the optimised PROTAC A13 was 26.4 nM. Further, A13 exhibited optimal protein degradation (85% degradation at 10 nM). Meantime, compared with PF-562271, PROTAC A13 exhibited better antiproliferative activity and anti-invasion ability in A549 cells. More, A13 had excellent plasma stability with T 1/2 >194.8 min. There are various signs that PROTAC A13 could be useful as expand tool for studying functions of FAK in biological system and as potential therapeutic agents.